QADZAF (MENUDUH BERZINA) MENURUT PERPEKSTIF HUKUM PIDANA ISLAM - Tiya, Birro; Hikmah, Nurul; Khalisatun Nurussaadah; Lahmudinur, Lahmudinur (PT. Pustaka Andil Lestari, 2025)
This study examines qadzaf, the act of accusing someone of adultery without valid evidence, from the perspective of Islamic criminal law while also addressing the challenges of slander dissemination in the digital era. Qadzaf is considered a serious violation as it can harm individual honor, disrupt lineage clarity, and create social tension. This research employs a descriptive qualitative approach through comprehensive literature review, with primary sources including Qur’anic exegesis, canonical Hadith collections (Kutub al-Sittah), and classical fiqh literature from the Hanafi, Maliki, Shafi‘i, and Hanbali schools. Secondary sources consist of modern academic books, journal articles, Islamic legal encyclopedias, and contemporary studies on digital ethics and the spread of slander on social media. Thematic analysis was conducted to identify definitions, legal elements, and the prescribed sanctions for qadzaf according to various scholars. Findings indicate that qadzaf involves three cumulative elements: accusation of adultery or denial of lineage without evidence, the accused being a muhshan (a Muslim, free, mature, sane, and of good moral standing), and the perpetrator’s unlawful intent. The prescribed punishment is eighty lashes as stated in Surah An-Nur verse 4, with scholarly differences regarding forgiveness; the Shafi‘i school allows victim pardon, whereas the Hanafi school mandates hadd implementation regardless of forgiveness. Qadzaf remains relevant in the digital age as a measure to prevent slander and protect human dignity. To enforce hadd, all elements must be fulfilled cumulatively, while ta’zir penalties can be applied if conditions are incomplete. The study emphasizes integrating classical fiqh teachings with modern challenges to address the widespread dissemination of digital slander.